UPAYA GURU TERHADAP PENGEMBANGAN KARAKTER KEJUJURAN DI SD/MI - Anjani, Astri Sekar Ayu; Herianingtyas, Nur Luthfi Rizqa (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This journal aims to investigate the efforts made by teachers in forming and strengthening the character of honesty at the Elementary School/Madrasah Ibtidaiyah (SD/MI) level. The character of honesty has an important role in forming a quality person and building a moral society. This study used a qualitative approach involving several teachers and students from several SD/MI who were randomly selected. Data were collected through interviews, observation, and related document analysis. The results showed that the teacher's efforts to form the character of honesty include several aspects. In conclusion, teachers play an important role in shaping the honesty character of students in SD/MI. Their efforts through teaching methods, real experiences, feedback, and supportive school policies can effectively build and strengthen students' honesty character. The implication of this research is the need for greater emphasis on developing the character of honesty in the curriculum and training of teachers to ensure that this value continues to be instilled in the younger generation as a solid moral foundation